AB0030 The effect of sildenafil and iloprost on cxcl10 level in systemic sclerosis: in vivo and in vitro comparison. (15th June 2017) - Antinozzi, C; Corinaldesi, C; Marampon, F; Riccieri, V; Valesini, G; Vasile, M; Lenzi, A; Galdo, F Del; Crescioli, C
Abstract : Background: Th1 cell/cytokine repertoire contributes to systemic sclerosis (SSc) pathogenesis from early autoimmune/vascular stages while Th2 dominance prevails later, when (multi)organ fibrosis occurs [1]. The Th1-type chemokine IFNγ-induced 10 kDa protein (CXCL10), involved in several autoimmune diseases (thyroiditis, rheumatoid arthritis, systemic lupus erythematosus, inflammatory myopathy) exerts detrimental effects at systemic and tissue/cell level; it is reported in association with more severe SSc prognosis [2–4]. Objectives: To compare circulating CXCL10 level in SSc patients starting iloprost (I), prostacyclin analogue with or without sildenafil (S), phosphodiesterase type 5 inhibitor, both vasoactive drugs used in SSc for Raynaud's phenomenon digital ischemic ulcers and/or secondary pulmonary arterial hypertension; SSc subjects under immunosuppressants (DMARDs) or corticosteroids (CCs) - first choice treatments at disease onset - before and after I were also evaluated. Intracellular path activation underlying Th1 cytokine-induced CXCL10 release by human skeletal muscle cells (Hfsmc), endothelial cells (Hfaec), cardiomyocytes (Hfcm) and fibroblasts (hFbs) were compared after iloprost or sildenafil. Methods: Sera of 27 SSc patients satisfying ACR/EULAR 2013 classification criteria for SSc were analyzed by ELISA before (T0, baseline) and 3 months after I intake (T3) vs. 15 age/gender-matched healthy subjects. Protein extracts from different human cell types were tested by Western blot for IFNγ+TNFα-induced NFkB, Stat1, JNK activation after S or I. Results: CXCL10 serum level was higher in all SSc under each drug/drug combination (range ∼300–500 pg/ml) vs. healthy subjects (∼150 pg/ml, P<0.05). I intake did not modify baseline CXCL10 in SSc subjects taking only I, DMARDs or CCs, while it significantly decreased CXCL10 in subjects under S (∼150 pg/ml, P<0.05). In Hfsmc S-induced inhibition of Stat-1/NFkB/JNK phosphorylation was higher vs. I (67/66/66% S vs. 28/30/38% I P<0.01). In Hfaec inhibition of Stat1/NFkB phosphorylation was higher and virtually prevented with I (99/92% I vs. 58/66% S P<0.01); conversely S-induced inhibition on JNK activation was significantly higher (66% S vs. 20% I P<0.01). In Hfcm I-induced inhibition was stronger on Stat1/JNK phosphorylation (67/83% I vs. 33/52% S P<0.05/P<0.01), while inhibition on NFkB was similar (70% I vs. 71% S). In hFbs, neither S nor I affected IFNγ+TNFα-induced activation of each analyzed path. Conclusions: Our in vivo results show that S and I combination is the more effective in targeting circulating CXCL10 in SSc patients. Our in vitro findings show a different inhibitory drug-induced effect onto paths underlying CXCL10 production, depending on cellular/intracellular targets. Thus, we suggest I and S combination as potential pharmacological tool in SSc not limited to treat vascular dysfunction but likely helpful to control different cell/tissue involvement and damage. References: Pattanaik D et al., Front Immunol 2015. Eloranta ML et al., Ann Rheum Dis 2010. Corrado A, Clin Ter 2014. Liu X et al., Arthritis Rheum 2013. Disclosure of Interest: None declared